Fiscal systems for hydrocarbons : design issues - Tordo, Silvana (World Bank working paper, 2007)
"This paper examines the key elements of the legal and fiscal frameworks used in the petroleum sector and aims to outline desirable features that should be considered in the design of fiscal policy with the objective of optimizing the host government's benefits, taking into account the effect this would have on the private sector's investment."--Jacket